Pembuatan dan Penggunaan Membran Selulosa Asetat untuk Pengolahan Air Berkapur - Deni Aldian (SAINS : Jurnal Kimia & Pendidikan Kimia, 2022)
Research has been carried out "Manufacture and Use of Cellulose Acetate Membranes for Limewater Treatment". This study aims to: (1) determine the selectivity of cellulose acetate membrane to Ca and Fe in lime water samples (2) The permeability of cellulose acetate membrane to lime water samples. The sample of this research is bore well water at the Fathul Mu'in Perdos Mosque, UHO's New Campus. This research consisted of several stages, namely the manufacture of cellulose acetate membranes with dimethylformamide additives, module manufacture, permeability tests and rejection tests which included determining the rejection coefficients of Fe and Ca. The composition of the cellulose acetate membrane used was cellulose acetate (11% w/w), dimethylformamide (20% w/w) and acetone (69% w/w) additives. The results showed that the membrane flux value was 43.99 L/m2 .Hour. and the rejection values for Fe and Ca metals were 61.04% and 10.467%, respectively.